2021
DOI: 10.1111/hae.14317
|View full text |Cite
|
Sign up to set email alerts
|

Validation of factor VIII activity for monitoring standard and extended half‐life products and correlation to thrombin generation assays

Abstract: Introduction Monitoring replacement therapy with standard and extended half‐life (EHL) products is challenging, since one‐stage assay (OSA) and chromogenic substrate assay (CSA) results may differ significantly. Recent recommendations include local validation of each new product with recovery within 20–30%, depending on activity level. Aim To validate factor VIII (FVIII) activity for monitoring products in clinical use on Atellica Coag and to correlate it with thrombin generation. Methods Plasma samples spiked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…However, the CSA‐2 could be useful when assaying post‐infusion samples of patients given EHL products. 5 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the CSA‐2 could be useful when assaying post‐infusion samples of patients given EHL products. 5 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 3 The need for CSA and OSA for factor activity measurement of FVIII and FIX is also demonstrated by assay discrepancy seen for extended half‐life (EHL) products, which was covered previously. 5 , 6 , 7 , 8 While high‐throughput and short turnaround times are essential requirements for coagulation analyzers in routine laboratories, the requirements for specialized laboratories that provide services to a hemophilia treatment center (HTC) are somewhat different. Besides correct phenotype and severity classification for hereditary bleeding disorders, testing also involves diagnosing acquired or treatment‐induced bleeding conditions, some of which are considered critical hemostasis tests (i.e., anti‐FXa activity for heparin/low molecular weight heparin [LMWH]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown a strong correlation between FVIII activity level and TG parameters (except for lag time) 4,5,21,24–28 . Despite these correlations, a wide inter‐patient variability in TG was observed when measured at different time points following a standard infusion of FVIII concentrate 4,21,24 .…”
Section: Factor VIII Concentratementioning
confidence: 99%
“…Multiple studies have shown a strong correlation between FVIII activity level and TG parameters (except for lag time). 4 , 5 , 21 , 24 , 25 , 26 , 27 , 28 Despite these correlations, a wide inter‐patient variability in TG was observed when measured at different time points following a standard infusion of FVIII concentrate. 4 , 21 , 24 However, the intra‐patient variability was small, resulting in a predictable relation between FVIII and TG for an individual patient.…”
Section: Factor VIII Concentratementioning
confidence: 99%